A Life-Course Analysis of Engagement in Violent Extremist Groups. (9th August 2019) - Carlsson, Christoffer; Rostami, Amir; Mondani, Hernan; Sturup, Joakim; Sarnecki, Jerzy; Edling, Christofer
Abstract: In this exploratory study, individuals' processes of engagement in violent extremist groups are analysed by drawing from criminological life-course theory and narrative-based understandings of crime. Based on interviews with individuals who have participated in violent extremism, it is suggested that the process of engagement consists of three steps: (1) a weakening of informal social controls, followed by (2) an interaction with individuals in proximity to the group and (3) a stage of meaning-making in relation to the group and one's identity, resulting in an individual's willingness and capacity to engaging in the group's activities, including violence. In future theorizing about processes of engagement in violent extremism, the meanings of age, and the life-course stages of late adolescence and emerging adulthood in particular, should be given analytic attention.